Endoscopic resection of a periampullary gangliocytic paraganglioma of the duodenum: A case report. (2016) - Paasch, Christoph; Hünerbein, Michael; Theissig, Franz
Highlights: The gangliocytic paraganglioma was resected endoscopically. Immunohistochemical examination reveal S100, synaptophysin and VIP expression. Abstract: Introduction: The gangliocytic paraganglioma (GP) is an extremely rare neuroendocrine tumour originating from the second part of the duodenum. Generally GP shows benign clinical behaviour. The GP is typically characterized by consisting of three tumour components: the epithelioid, the spindle-shaped and the ganglion-like cells. Presentation of case: We present a female patient at the age of 65, who underwent a routine gastroscopy due to known gastro-oesophageal reflux. Accidentally a 2 × 1, 5 cm sized mass of unknown entity was revealed in the duodenum. The magnet resonance tomography neither detected distant metastasis nor any local lymphadenopathy. After endosonographically guided punctures of the submucosal mass, a malignant tumour could not be diagnosed thus the decision to perform an endoscopical resection was made and successfully conducted. Immunohistochemical examination revealed a total resected GP. Discussion: In literature malignant transformation with distant metastasis and local recurrences has been described. Furthermore the clinical manifestation and location varies. The GP has often been misdiagnosed as an euroe ndocrinet umour (NET) G1. Conclusion: Due to published cases of metastasising GPs, we recommend a long term follow-up. In a non-metastatic stage the endoscopic resection should be the therapy of choice in order to prevent unnecessary major surgical interventions. In this case report we will discuss the clinical appearance, behaviour and differential diagnosis of GP.